Análisis biomecánico del pie protésico Bioc-dm2 - Jhon Hernandez Martin (Editorial Universitaria, 2019)
Walking is one of the aspects directly compromising human wellbeing, as it has a physical and emotional impact in daily life. For this study, we delve into the challenge of improving some walking conditions in a patient suffering lower limb loss, specifically at transtibial or transfemoral levels. Given that our purpose was the analysis, design and manufacture of a lower-limb prosthetic component, which fills the needs for functionality, it became necessary to build a foot with all the quality standards associated to each and all movements required to form the complex fundamental pattern of walking. Besides, this foot should also easily endure weight, daily use and physical characteristics of the patient object of this study. When performing physical validation and during human walk, a proper response is observed in terms of mechanics, materials and dynamics of the component, thus making evident proper construction and assembly. On the other hand, it is feasible that design and verification of the component provided a competitive element, as compared to existing elements currently in the market. The previous situation generated the need for verification from the National Institute for Medications and Food (INVIMA), as well as the revision of the use replying device, for component verification, in accordance with ISO 10328.